Radon exhalation rate from the latex pillows and its potential exposure to users - Phachirarat Sola; Kanokporn Boonsirichai; Santi Raksawong; Ritiron Samran; Pimprapa Chaijak; Hirofumi Tazoe; Chutima Kranrod; Rawiwan Kritsananuwat; Sattawat Jongjitklang; Vichai Puripunyavanich; Masahiro Hosoda; Waleeporn Pongkua; et al. (Radiation Medicine and Protection)
Objective: To develop a new system to accurately measure the radon exhalation from the latex pillows, and to estimate its potential exposure to users. Methods: The new system is composed of two loops, the first loop is designed to trap background radon and thoron until their levels are nearly zero, and the second loop is the measurement loop to detect radon and thoron exhalation rates from the pillows. Results: The results showed that mass radon exhalation rated ranged from 0.18 Bq·kg−1⋅h−1 to 0.78 Bq·kg−1⋅h−1, with an average of (0.36 ​± ​0.17) Bq·kg−1⋅h−1 in the 9 samples. The average annual effective dose to users in a model room was estimated to be (15.51 ​± ​12.69) μSv by assuming two pillows was used. Conclusion: These results demonstrate that the new system can effectively measure radon exhalation rates in latex pillows, and the potential exposure to radon exhalating from the pillows is very low.